FISH BOMBS : FOR BUSINESS MOTIVES OR BASIC NEEDS - Ahdan Ahdan (Salewangang Institut Publishing, 2018)
This study intended to inform the social construction about the actions of fishermen in Lumulumu Island using fishing bomb. The focus of the study is on large and small fishermen based on business or commercial motives and motives to fulfill basic needs. Specifically, this research is more oriented to the meanings constructed by fishermen behind the use of fish bombs. This research emphasizes more on the emic perspective, with the understanding that the information gathered from the fishermen is described based on expressions, ways of thinking and interpretations of the subjects themselves, so that it can be revealed what is hidden behind their actions using fish bombs. Fishing bombs fishermen in the study area consisted of two types or categories, first, large-type (lompo) bombs fishermen called paEs with status as punggawa and secondly, small-type fishermen (caddi) called independent fishermen (sawi). The status of small fishermen generally as sawi. Researcher's findings, fishermen on Lumulumu Island took action to use fishing bombs not based on awareness based on knowledge but because of economic motives to meet basic needs and partially follow it. This reality is shown by the low education of fishermen, the reduction of bomb fishermen due to changing professions, and the disinterest of some fishermen in fish bombs. In other words, the fishermen using fish bombs are not based on internalization, but rather acts of deviation from legitimate legal norms with motives to meet family needs and business motives.